Pengembangan Produk Life Jacket Yang Terintegrasi Dengan Jas Hujan Bagi Nelayan Pelabuhan Perikanan Pantai Sadeng Dengan Menggunakan Metode Quality Function Deployment (QFD) - Rudiyanto, Rudiyanto; Zabidi, Yasrin; Uyuunul Mauidzoh (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Occupational health and safety (K3) is the most important factor in worker productivity and reduces the risk of accidents that can harm workers, as is the implementation of K3 on fishermen from PPP Sadeng who have a high level of risk. integrated with the raincoat. The method used in this research is Quality Function Deployment (QFD). The instruments in this study are needs analysis questionnaires, anthropometric measurements, and QFD questionnaires. , Durable materials, lightweight materials, ease of use, and attractive shapes, 2.) Prototype sizes will be divided into 3 parts, namely M, L, and XL, the distribution of these 3 sizes is intended so that consumers get the appropriate and comfortable size when used. Size M refers to the 5th percentile, size L refers to the 50th percentile, and size XL refers to the 95th percentile. Keywords: life Jacket, Ergonomics, Anthropometry,QFD